Metropoliten alanlarda planlama-kent yönetimi ilişkileri ve İstanbul metropoliten alanında planlama yönetimine ilişkin bir model denemesi - Ramazanoğulları Turgut, Sırma (My University, 2000)
The globalization fact which began to be effectual all over the world beginning from the '80 ps on, has forced the societies in a process of metamorphosis and transformation in almost fevery field. The units on which the spacial reflections of these changes are examined at the most are the cities. The transformation in guestion has also braught with it recodification and E" lentification of the contents of consents and relations The changing of the social system ctural factors and the change in the way these systems work have brought into agenda new les concepts, standarts, rules, institutions and the way these institutions. Are being administrated. This transformation and mutual affectiveness movement which has nothing to do will spacial or time limits is being felt even stronger in metropolitan areas. In context with the new contentsof the concepts "space" and "local". The metropolitan areas gaining a new identity parallel to the network they take place in, have become an "administrative focus" as a result of metropolitan areas that have gained the right to catchattraction due to their local potential and their will power, have gained even more importancein international competition parallel to these changes. Of course the metropoliten areas and their administration that display a very flexible and dynamic structure, must not be considered in astandart and static frame. Otherwise it is possible that planning loses its function. Becouse planning is a case which works as a whole together with urban administration process and structure of organization urban administration in metropolitan areas. And planning cases which are integrated with each other as a "whole of systems" must work together and in harmony if we are to speak abaut "planning administration". And it would ten be possible for the planning to reach its goals in spite of the changing conditions and without losing its neutrality and so would it be possible to supervise it efficiently. i The basic starting point of this work is that planning has lost its effectiveness in the Istanbul Metropolitan Area and thus is far from being able to achieve its goals and the main causes of these problems lie in the fact that the urban management. And the planning processes are "slow" and "clumsy" and dose not much conicide with each other thus resulting in a structur that hinders planning " This research consist of seven parts: The First Chapter: The aim of the work, its limits, methodes and assumptions are introduced. The Second Chapter: It has been pointed out that due to its particular characteristic, capitalism is a continuous process of change and evoluation. In connectioa With these the facts of fordism and postfordism and the process / cocepts which are defined by these idetifications. Also the effects and transformation relized in these identifications pressure, experienced durin various production processes, on the social sructure, the city and urban administration are defined. The Third Chapter: The transformation movements that are stated in the previous chapter pertaining to local administration and specially urban administration are considered at length and the oretical discriptions are made. In this part a side from the changes in the theoretical discriptions in time, the fact of "urban management" taking place in the frame of a systems analysis, to define in connection with the series of management, public management, local management, urban management and the management of the metropolitan area and their interaction has been brought in to attention In both this part and in the survey as a whole, the unit of management defined as urban management is "belediye" and the unite defined as Istanbul Metropolitan Area is accepted as the municipality of Metropolitan Area. xiiiThe Fourth Chapter: In this chapter management & planning relations at Istanbul Metropolitan Area are concidered in three main periods. These periods are defined as a) Tanzimat - The Republican Period b) The Republican Period - Planned Period c) Planned Period - Today. At the end of the chapter a detailed analysis of Istanbul Metropolitan Area management and planning relations are presented and present conditions are fixed so as to distinguish the problem that forms the starting point of this research. The Fifth Chapter: In this chapter, taking the present conditions as a cross section, a detailed analysis of the interrelations between the İstanbul Metropolitan Area has been presented and upon making some fixations concerning present conditions, the problem (caos) that forms the starting point of this study has been defined. The factors that have been established concerning the existing situation. The Sixth Chapter: A proposal for the model for the model of Management of Planning has been realized via new urban management system that has been aimed for the İstanbul Metropolitan Area in the light of evaluations mad before as a result. The Seventh Chapter: In the last chapter results and proposals are presentedA special management model unigue to the Istanbul Metropolitan Area has to be formulated. It has been pointed out that only in such a system can the concept of planning really work out and keep on being effective continuously. Attention has been called uponthe fact that the Istanbul Metropolitan Area has a very strategic and dynamic imporatnce in context with both international and national relations and thus can direct this dynamism and potentials towards the benefits of the lcity" and the "citizen" in the long run. Moreover, it has been pointed out that thereis an intensive and immediate need for a new management and planning system that can protect different balances within the elasticity limits of ur era and the basic acceptence for a new model that is aimed to realize in responce to the needs of the city in line with the given factors, keeping in mind the assumptions put foreword in this work, are set down, to say the last word, the majority of İstanbul Metropolitan Area must be the main managerial unit that supervised the whole Metropolitan Area and it's all kinds of relations and it must also be reponsible of the coordination and orientation function at each stage in respect with the macro to micro levels of activity. The wholeness of this system will be realized when the legal, organizational system and the operational system and the opertation line will all be concidered in a systematic approach. The planning and its discipline must be in such a form that will back up the metropolitan formation and its orientation with the management and the caos that leads to a total collapse must definetly be lindered. The most important philosophy for the new model to be formed with this goal must be one that is purified from caos and contradictions, that reorginezes the wholeness and protects, beginning from the upper scale goals and strategic resolutions going down to making projects and ewisioning levels that is legalized and a planning concept accepted by all the actors of the city.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2000
Keywords: Toplumsal-kavramsal dönüşüm ve kent yönetimi olgusu; Yerel yönetim kavramı yerel yönetimlerde değişim süreci ve kuramsal açıklamalar; Tarihsel süreç içerisinde istanbul metropoliten alan'ında yönetim ve planlama ilişkileri; Günümüz istanbul metropoliten alan'ında planlama yönetimine ilişkin bir model denemesi